PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN POWERPOINT INTERAKTIF TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN 02 LUBUK BUAYA KOTA PADANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the impact of using the Problem Based Learning approach with Interactive PowerPoint on improving learning outcomes in class IV SDN 02 Lubuk Buaya, Padang City. The background is the discovery of observations where learning in the classroom is still the center of the teacher. Students lack engagement, are unaccustomed to discussion, and the use of interactive learning media remains minimal. The study used a quasi-experimental design with a nonequivalent control group and a quantitative methodology. The sample consisted of two groups, namely the experimental class and the control class totaling 54 students with 27 students each. The assessment instrument used was a multiple-choice objective test that had been validated for both validity and reliability. The research findings showed that the average Pre-Test result of the experimental class was 51.07 and the control class was 52.22 with the hypothesis test showing no significant difference (Sig. 0.755 > 0.05), meaning the initial proficiency levels of both classes were equivalent. After the intervention, the post-test score for the experimental class was 78.07 was superior when referred to the control class of 67.15. Using the Independent Sample T-Test for the hypothesis test, the Sig. value was found to be 0.001 < 0.05. Thus, it can be concluded that the application of the Problem Based Learning model assisted by Interactive PowerPoint has a significant effect on student learning outcomes in science learning for grade IV of SDN 02 Lubuk Buaya, Padang City.